Vitamin B1 in marine sediments: pore water concentration gradient drives benthic flux with potential biological implications - Monteverde, Danielle R.; Gómez-Consarnau, Laura; Cutter, Lynda; Chong, Lauren; Berelson, William; Sañudo-Wilhelmy, Sergio A. (Frontiers in Microbiology, 2015)
Vitamin B1, or thiamin, can limit primary productivity in marine environments, however the major marine environmental sources of this essential coenzyme remain largely unknown. Vitamin B1 can only be produced by organisms that possess its complete synthesis pathway, while other organisms meet their cellular B1 quota by scavenging the coenzyme from exogenous sources. Due to high bacterial cell density and diversity, marine sediments could represent some of the highest concentrations of putative B1 producers, yet these environments have received little attention as a possible source of B1 to the overlying water column. Here we report the first dissolved pore water profiles of B1 measured in cores collected in two consecutive years from Santa Monica Basin, CA. Vitamin B1 concentrations were fairly consistent between the two years ranging from 30 pM up to 770 pM. A consistent maximum at ~5 cm sediment depth covaried with dissolved concentrations of iron. Pore water concentrations were higher than water column levels and represented some of the highest known environmental concentrations of B1 measured to date, (over two times higher than maximum water column concentrations) suggesting increased rates of cellular production and release within the sediments. A one dimensional diffusion-transport model applied to the B1 profile was used to estimate a diffusive benthic flux of ~0.7 nmol m 2 d-1. This is an estimated flux across the sediment-water interface in a deep sea basin; if similar magnitude B-vitamin fluxes occur in shallow coastal waters, benthic input could prove to be a significant B1-source to the water column and may play an important role in supplying this organic growth factor to auxotrophic primary producers.